Consumer psychology of tourism, hospitality and leisure - Crouch, G. I.; Crouch, G. I.; Perdue, R. R.; Perdue, R. R.; Timmermans, H. J. P.; Timmermans, H. J. P.; Uysal, M.; Uysal, M. (Wallingford :CABI Publishing, 2004)
This book focuses on consumer behaviour in the context of tourism, hospitality and leisure. It comprises of 8 parts that discuss: attitudes, emotions and information processing; motivation and learning; consumption systems; decision and choice; experience and satisfaction; market segmentation; attraction and loyalty; and image and interpretation. The book consists of 26 chapters and is indexed.
Keywords: CC300 - Information and Documentation; EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); EE700 - Marketing and Distribution; EE720 - Consumer Economics; UU485 - Social Psychology and Social Anthropology, (New March 2000); UU600 - Leisure; UU700 - Tourism and Travel